2021
DOI: 10.1088/1361-6463/abfefc
|View full text |Cite
|
Sign up to set email alerts
|

Factors triggering germination in plasma-activated cotton seeds: water imbibition vs. reactive species’ formation

Abstract: E Arroyo et alanalysis by FT-IR of the adsorption of deuterated water (D 2 O) molecules is proposed as a useful procedure to directly monitor water uptake/release processes from seed surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…This can be directly inferenced when treating the seeds with H 2 O 2 , [ 41–45,48 ] but it is not so evident for the plasma treatments where the role of RONS in activating the germination is still a likely hypothesis. [ 5,49 ] In the present study with barley seeds, hints by XPS suggest the formation of similar species upon plasma treatment. In recent work, the formation of very reactive radical species in barley seeds subjected to plasma treatments has been proved by electron paramagnetic resonance.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…This can be directly inferenced when treating the seeds with H 2 O 2 , [ 41–45,48 ] but it is not so evident for the plasma treatments where the role of RONS in activating the germination is still a likely hypothesis. [ 5,49 ] In the present study with barley seeds, hints by XPS suggest the formation of similar species upon plasma treatment. In recent work, the formation of very reactive radical species in barley seeds subjected to plasma treatments has been proved by electron paramagnetic resonance.…”
Section: Resultsmentioning
confidence: 49%
“…Similar behavior has been found by us for quinoa and cotton seeds exposed to plasma treatments. [ 5,49 ] These evidence revealed that although the surface topographic changes induced by plasma are not quite significant, a certain mobilization and out‐diffusion of some elements takes place as a result of this treatment. We tentatively propose that the observed diffusion of elements likely responds to changes in chemical potential induced at the surface by the plasma treatments.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations